(untitled) (Journal of Monno Medical College, 2024)
Background: Restoration of effective vision is the principal aim of all modalities of cataract surgery including Phacoemulsification. Energy level of ultrasonic power in Phacoemulsification and turbulence of fluid in the anterior chamber plays an important role in corneal endothelial cell loss influencing post-operative corneal clarity. Objectives: To compare post-operative corneal clarity after Phacoemulsification by two techniques of nuclear divisions: stop and chop with divide and conquer. Methodology: This prospective observational study was conducted at Shaheed Monsur Ali Medical College and Hospital, Uttara, Dhaka from January, 2023 to June, 2023. The study was carried out on 30 outdoor patients undergoing Phacoemulsification at SMAMCH and Mirpur Eye Hospital, Dhaka. The selected patients underwent detailed ocular and systemic examinations with relevant investigations and divided equally into two groups comprising of 15 in group A (stop and chop) and 15 in group B (divide and conquer). Phacoemulsification was done in all patients by a single expert surgeon. Patients were followed up after 1 week, 4 weeks and 12 weeks of surgery. Corneal endothelial cell count and central corneal thickness were assessed in each visit. Mean value of these mentioned parameters in follow-up periods were compared between two groups. Unpaired t test was done to assess the level of significance. Results: The mean age + standard deviation (SD) of the study subjects was 61.5+2 years, out of which 13(43.33%) were males and other 17(56.67%) females. Pre-operative value of mean endothelial cell count was 2620+70.20/mm2 in group A and 2625+71.10/mm2 in group B. Postoperative mean value + SD of endothelial cell count was 2420+68.90/mm2, 2345+66.64/mm2, 2310+66.04/mm2 respectively after 1 week, 4 weeks and 12 weeks of surgery in group A and 2410+69.54/mm2, 2340 +6587/mm2, 2310+64.45/mm2 in group B respectively. Mean value + SD of central corneal thickness was 545+40.50 micrometer, 535+40.02 micrometer and 532+39.85 micrometer respectively after 1 week, 4 weeks and 12 weeks after surgery in group A and 547+43.98 micrometer, 537+41.23 micrometer and 533+40.63 micrometer respectively in group B. Conclusion: Quantitative assessment and comparison of endothelial cell count and central corneal thickness shows that at end of the study, there was no remarkable difference in mean values of endothelial cell count and central corneal thickness between two methods. Journal of Monno Medical College December, 2023; 9 (2):37-40